Perineural dexamethasone in ultrasound-guided interscalene brachial plexus block with levobupivacaine for shoulder arthroscopic surgery in the outpatient setting: randomized controlled trial - Vasconcelos,Mateus Meira (2020)
Abstract Background and objectives: In shoulder arthroscopy, on an outpatient basis, the patient needs a good control of the postoperative pain that can be achieved through regional blocks. Perineural dexamethasone may prolong the effect of these blocks. The aim of this study was to evaluate the effect of perineural dexamethasone on the prolongation of the sensory block in the postoperative period for arthroscopic shoulder surgery in outpatient setting. Methods: After approval by the Research Ethics Committee and informed consent, patients undergoing arthroscopic shoulder surgery under general anesthesia and ultrasound-guided interscalene brachial plexus block were randomized into Group D - blockade performed with 30 mL of 0.5% levobupivacaine with vasoconstrictor and 6 mg (1.5 mL) of dexamethasone and Group C - 30 mL of 0.5% levobupivacaine with vasoconstrictor and 1.5 mL of 0.9% saline. The duration of the sensory block was evaluated in 4 postoperative moments (0, 4, 12 and 24 hours) as well as the need for rescue analgesia, nausea and vomiting incidence, and Visual Analog Pain Scale (VAS). Results: Seventy-four patients were recruited and 71 completed the study (Group C, n = 37; Group D, n = 34). Our findings showed a prolongation of the mean time of the sensitive blockade in Group D (1440 ± 0 min vs. 1267 ± 164 min, p < 0.001). It was observed that Group C had a higher mean pain score according to VAS (2.08 ± 1.72 vs. 0.02 ± 0.17, p < 0.001) and a greater number of patients (68.4% vs. 0%, p < 0.001) required rescue analgesia in the first 24 hours. The incidence of postoperative nausea and vomiting was not statistically significant. Conclusion: Perineural dexamethasone significantly prolonged the sensory blockade promoted by levobupivacaine in interscalene brachial plexus block, reduced pain intensity and rescue analgesia needs in the postoperative period.